2018
DOI: 10.3354/esr00900
|View full text |Cite
|
Sign up to set email alerts
|

Variation in home range size and patterns in adult female American crocodiles Crocodylus acutus

Abstract: The American crocodile Crocodylus acutus is a threatened species that uses relatively deep, open-water habitats with low salinity. Adult female American crocodiles nest on sandy coastal beaches, islands or human-made berms, assist in the hatching process, and can travel long distances to nesting habitat. We satellite-tracked 15 adult female American crocodiles in 2 hydrologically distinct areas in Everglades National Park, Florida, USA, to quantify the home range sizes, test for intraspecific differences in ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
1
8
1
Order By: Relevance
“…This supports the hypothesis that freshwater diversion and the associated deterioration of habitat conditions in NEFB, an area that has historically supported high crocodile numbers, has negatively impacted the health and abundance of crocodiles there [22,28,30]. Crocodile numbers have increased in FLAM and CAPE areas [22,79], which is likely due to the cumulative effects of ongoing restoration efforts near these areas (Table 1). The plug at Buttonwood Canal may have reduced saltwater intrusion northward and improved nursery habitat in this area (Table 1).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This supports the hypothesis that freshwater diversion and the associated deterioration of habitat conditions in NEFB, an area that has historically supported high crocodile numbers, has negatively impacted the health and abundance of crocodiles there [22,28,30]. Crocodile numbers have increased in FLAM and CAPE areas [22,79], which is likely due to the cumulative effects of ongoing restoration efforts near these areas (Table 1). The plug at Buttonwood Canal may have reduced saltwater intrusion northward and improved nursery habitat in this area (Table 1).…”
Section: Discussionsupporting
confidence: 72%
“…By age six, subadult crocodiles have a 90% survival rate that continues into adulthood. The first few years of a crocodile's life are critical and are directly related to experiences during the first six months of life [26] and may be an indicator of environmental conditions [79]. Survival rates were highest in CRL (69%) and FLAM (53%) and much lower in NEFB (34%) and MADB (31%) areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last months of study, our data show that M. niger and C. yacare have the lowest average HR recorded, as compared to other studies. When reviewing the published HR data for crocodylians, it becomes clear that there is a large difference between the sizes of the HR reported, with the lowest average for Tomistoma schlegelii with 0.8 ha (Bonke et al, 2014) and the largest for Crocodylus acutus with 8436 ha (Beauchamp et al, 2018). Despite this large range in HR of crocodylians, we were surprised that MR's reported during the last month of our study were smaller than those reported for all other crocodylian species.…”
mentioning
confidence: 99%
“…Comprehensive studies of spatial ecology have been undertaken on many crocodylian species using a variety of methods. These studies have improved our knowledge on movement patterns and home range of Alligator mississippiensis (Rodda, 1984; Rootes & Chabreck, 1993; Rosenblatt et al, 2013), Alligator sinensis (Ding et al, 2004), Caiman yacare (Campos et al, 2006), Crocodylus acutus (Balaguera‐Reina et al, 2016; Beauchamp et al, 2018), Crocodylus intermedius (Munoz & Thorbjarnarson, 2000), Crocodylus johnstoni (Tucker et al, 1997), Crocodylus niloticus (Calverley & Downs, 2015; Combrink et al, 2017; Hutton, 1989), Crocodylus porosus (Brien et al, 2008; Campbell et al, 2013; Kay, 2004; Read et al, 2007), Gavialis gangeticus (Lang & Whitaker, 2010), Melanosuchus niger (Martin & da Silva, 1998), Paleosuchus trigonatus (Magnusson & Lima, 1991) and Tomistoma schlegelii (Bonke et al, 2014). Habitat use, homing abilities, dispersal and social interactions have also been described for some species (Balaguera‐Reina et al, 2016; Goodwin & Marion, 1979; Hutton, 1989; Read et al, 2007; Rodda, 1984; Rosenblatt et al, 2013; Tucker et al, 1997).…”
Section: Introductionmentioning
confidence: 98%